The era of multiple biologics: Is combination and switching an option in the management of severe asthma? - Okwuofu, Emmanuel Oshiogwe; Yong, Audrey Chee Hui; Lim, Jonathan Chee Woei; Stanslas, Johnson (Academic Press, 2025)
Background and objective: The introduction of biologics therapies targeting specific cytokines relevant to asthma pathophysiology has changed the landscape in the treatment of severe asthma in both adults and children. However, the availability of multiple agents, inclusion criteria for randomised control trials (RCTs), variation in national and international guidelines, instances of treatment failures, and the potential of switching or combining biologic therapies, highlight the need for real-world evidence. Data from real-world studies of biologics in severe asthma may complement efficacy data obtained from RCTs and provide important post-marketing safety information. Additionally, these studies may help inform the design of future clinical trials, characterise the natural history of the disease, and support important translational research. This review highlights current evidence for the combination and switching of biologics in severe asthma and comorbid diseases that may serve as pointers for optimal clinical outcomes. Method: Pubmed, Scopus, and Web of Science were searched using specified search strategies. Results: Available evidence suggests that patients with severe asthma who received combination or switched biologics (omalizumab, benralizumab, reslizumab, mepolizumab, dupilumab, and Tezepelumab) in real-world settings experienced significant improvement in asthma control, exacerbation, and lung function. Although combining biologics is not currently a common practice, there are cases where biologic therapies were combined, discontinued, or switched. Conclusion: Patients may benefit from the early and systematic consideration of combination and switching of biologic therapies in severe asthma.